Methodological alternative to improve tactical thinking to Tashi Waza in judo athletes of Pinar del Río/Alternativa metodológica para mejorar el pensamiento táctico al Tashi Waza en los atletas de judo de Pinar del Río - Osviel Hernández Sotolongo; Esteban Eddy Méndez Lazo; Ramón Martínez Vidal; Marcia Caridad Lanza Hernández (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The contemporary stage of sport development has certain characteristics that exert a great influence on the organization of the preparation and training of athletes, determining for the coach new tasks and more complex demands. The present work had as objective to design a methodological alternative for the improvement of tactical thinking to Tashi Waza in judo athletes, category 15-16 years old, of the Initial Sport School (Eide in Spanish) of Pinar del Rio. To get into the subject, the most important characteristics of judo strategy and tactics were outlined, as well as the essential principles that support them. In addition, the convenience of using auxiliary forms in the technical-tactical preparation and training of the judo athletes was pointed out. The study continued with a light analysis applied to judo as a relevant variable in the development of tactical thinking. Emphasis was placed on the different types of tactics in judo combat, as well as on the psychomotor processes in each of the phases of combat, all this taking into account the particularities of athletes at these ages. The empirical scientific methods used were observation and interview, and the theoretical ones were historical-logical and synthesis analysis, which offered greater rigor to the research. The idea of investigating the tactical thinking in judo arose a few years ago, in response to the question of teaching athletes to solve by themselves the innumerable problems that arise in combat.